The translation techniques, processes and important tools to achieve a high quality translation - Hernández Rivera, Gerardo Antonio
The specialization course, Fundamentals and Translation Techniques, focused on the practice and theory of the translation process. The basic concepts, application, and study of the main techniques for the translation process and other related topics were learned through the completion of guides, tasks, and weekly exercises to learn more about their use and implementation in the current context. In the first module, the history and myths of translation were studied, along with the concepts and techniques that can be used in the translation process. The second module of this specialization course was named “The Process of Translation” which was about creating a translation process. First of all, the teacher taught a lot of processes created by other translators in order to see and have an idea of how to elaborate the translation process. After that, the teacher assigned homework in which it was necessary to choose a paragraph to put into practice the translation process to be presented in a PowerPoint presentation in front of the teacher and classmates. After finishing module two, module three was next, which was called “The translation tools”. In this module, the teacher presented various tools that can help make a better translation. This module was about a lot of programs that can facilitate translation work. Some of these tools were, for example; Babilone, Cafetrans, ProZ, Photopea, and others. In this module, a practice was assigned which consisted of translating a car manual and applying the translation tools. These tools can be used but it does not mean that the task was done, all translators have to revise since the text always has some mistakes that need to be fixed. In the fourth module “Translation Practices” was characterized by putting into practice what was studied and learned in the previous modules as the basic concepts, the different processes to develop different techniques, and the use of different technological programs that can help translators to perform a professional translation process. During this specialization course translation techniques were learned and programs available on the internet were used for translation to achieve the best standards that today's world needs, as well as the work to be presented, is professional, logical, and in accordance with the target language to be translated.